Trends in manner and cause of death over a 10-year period (2007–2016) at a regional forensic pathology facility, Cape Town, South Africa. (29th July 2019) - Mole, Calvin Gerald
ABSTRACT: Salt River Medico-Legal Laboratory (SRMLL), services the West metropole of the City of Cape Town, South Africa. Medico-legal autopsies are performed on any individual suspected of having died by other than natural causes, and they are governed by relevant legislation. The aim of the current study was to determine the trends of medico-legal autopsies conducted at SRMLL. As such, a retrospective review was conducted on the intake data of all autopsies performed between 2007 and 2016. A total of 32, 127 autopsies were conducted during this period, the majority (32.7%) of which were suspected homicide cases, followed by unexpected deaths and road traffic accidents. The analysis indicated that the number of medico-legal autopsies performed was fairly stable until 2011, when a sharply increasing trend emerged, continuing to 2016. A similar trend in homicide cases was noted. The prevalence of sharp force trauma remained relatively constant and was initially the predominant form of trauma; however, in 2012 ballistic trauma began to rapidly increase and predominated as the method of homicide. It is evident that greater intervention is needed to curb gun violence in South Africa.